2013
DOI: 10.1109/tro.2013.2257581
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Controller and Observer for a Magnetic Microrobot

Abstract: Abstract-The present paper discusses the control design of a magnetically-guided microrobotic system in blood vessels to perform minimally invasive medical procedures. Such microrobots consist of a polymer binded aggregate of nanosized ferromagnetic particles and a possible payload that can be propelled by the gradient coils of a magnetic device. A fine modeling is developed and used to define an optimal trajectory which minimizes the control efforts. We then synthesize an adaptive backstepping law that ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 34 publications
0
45
0
1
Order By: Relevance
“…Proof: Properties (P1) and (P2) have been demonstrated in [15] and [20], respectively. In particular, the local controllability of system (7) is inherited from the controllability of its linearized time-variant system along the reference trajectory z ref (t) [21], [22].…”
Section: Lemma 1 Letmentioning
confidence: 88%
“…Proof: Properties (P1) and (P2) have been demonstrated in [15] and [20], respectively. In particular, the local controllability of system (7) is inherited from the controllability of its linearized time-variant system along the reference trajectory z ref (t) [21], [22].…”
Section: Lemma 1 Letmentioning
confidence: 88%
“…In our review of the literature, we only found two attempts at advanced kinematic path planning of untethered microrobots other than simple waypoint selection. The first is in [14], where an optimal path was generated to limit the control effort required to move a microrobot through pulsing blood flow. In [15], the fast marching method (FMM) was used to solve the path planning problem between a start and end position in a blood vessel.…”
Section: A Motion Planningmentioning
confidence: 99%
“…In [20] time delay estimation (TDE) was used to account for uncertainty in parameters associated with nonlinear dynamics in the system model. In [14], nonlinear adaptive control was considered for a magnetically-pulled microrobot navigating through endovascular blood vessels. Backstepping was used to generate a control law that is Lyapunov-stable about a trajectory given linear uncertain parameters in the dynamics.…”
Section: B Motion Controlmentioning
confidence: 99%
“…A control module ( ) generates the magnetic gradient field to propel the microcarrier. Different control schemes have been sucessfully tested, such as a proportional-integral-derivative (PID) controller [15] , predictive controller [16] , or adaptive backstepping controller [17] . Moreover, the overall concept of the MRI-tracking system is based on the fact that both tracking and propulsion are possible with the manufacturer-supplied gradient coils of the MRI system.…”
Section: Introductionmentioning
confidence: 99%